Reef effect of offshore structures on the occurrence and foraging activity of harbour porpoises - Fernandez-Betelu, Oihane; Graham, Isla M.; Thompson, Paul M. (Frontiers in Marine Science, 2022)
With increasing numbers of offshore structures being installed and decommissioned, a better understanding of their effect on marine predators is timely. There is some evidence that oil and gas platforms may attract marine mammals, acting as artificial reefs. However, it is unclear whether different man-made structure designs have similar effects or whether artificial structures modify the diel patterns of occurrence and foraging of marine mammals. Here, we used passive acoustics to investigate the occurrence and foraging activity of harbour porpoises (Phocoena phocoena) around four artificial structures of different age and complexity. We deployed an array of echolocation click detectors (CPODs) in 2021, along a gradient of distances to these structures and assessed the extent to which porpoises were attracted to them and their effect on porpoises’ diel patterns of occurrence and foraging activity. The probability of porpoise occurrence and foraging activity decreased with distance from offshore structures. A significant increase in porpoise occurrence and foraging was detected during night-time compared to daytime around all four offshore structures (< 200 m). Comparing pre- and post-installation porpoise detections, the daily patterns of occurrence and foraging activity shifted from a weak diel pattern before the structure was installed, to a strong nocturnal pattern when the structure was present. These findings provide evidence that marine mammals are attracted to man-made structures and that porpoises modify their diel patterns of occurrence and foraging activity around them. This research suggests that offshore structures play an important role as foraging areas for some marine mammals and provides key information for decommissioning considerations and the planning of decommissioning activities.